1999
DOI: 10.1524/ract.1999.85.12.79
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Synergistic Extraction of Octahedral Co(II) from Nitrate Medium by 8-Hydroxyquinoline-Db18C6 Chloroform Mixture

Abstract: The kinetics of extraction of radioactive octahedral Co(n) by a Chloroform mixture of 8-hydroxyquinoline (HOX) and dibenzo-18-crown-6 (Dbl8C6) from nitrate medium was investigated using a stirred Lewis cell. The effects of the stirring speed, temperature, specific interfacial area and interfacial tension on the extraction rate showed that the extraction process is controlled by a chemical reaction in the bulk aqueous phase rather than at the interface. The results of the effect of [HOX], [Dbl8C6] and [H^] on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…111,112 The solvent extraction dependencies led to the formulation Co(L) 2 (DB18C6), 112 and subsequent extraction kinetics experiments have concluded that the rate-limiting process is the aqueous phase complexation of Co(II) by 8-hydroxyquinoline. 111 These findings contrast those reported for the Eu(III)/ 18C6/HTTA system in which interfacial chemical reac-tions are identified as rate limiting, 60 but the findings are not unexpected considering that 8-hydroxyquinoline is less organophilic than HTTA. The rather low distribution constant (K D ) of 8-hydroxyquinoline contributes to its limited utility as a chelating extractant.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…111,112 The solvent extraction dependencies led to the formulation Co(L) 2 (DB18C6), 112 and subsequent extraction kinetics experiments have concluded that the rate-limiting process is the aqueous phase complexation of Co(II) by 8-hydroxyquinoline. 111 These findings contrast those reported for the Eu(III)/ 18C6/HTTA system in which interfacial chemical reac-tions are identified as rate limiting, 60 but the findings are not unexpected considering that 8-hydroxyquinoline is less organophilic than HTTA. The rather low distribution constant (K D ) of 8-hydroxyquinoline contributes to its limited utility as a chelating extractant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(c) Other Chelating Extractants . Two reports have appeared that discuss the extraction of octahedral Co(II) complexes from NO 3 - media by DB18C6 and 8-hydroxyquinoline in CHCl 3 . , The solvent extraction dependencies led to the formulation Co(L) 2 (DB18C6), and subsequent extraction kinetics experiments have concluded that the rate-limiting process is the aqueous phase complexation of Co(II) by 8-hydroxyquinoline but the findings are not unexpected considering that 8-hydroxyquinoline is less organophilic than HTTA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…23 Only a few papers dealing with the extraction of Co(II) with mixtures of 8-hydroxyquinoline and DB18C6 have been published. 24,25 This provoked interest in extraction systems containing HQ, as a part of systematic studies of synergistic solvent extraction and the separation of lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%
“…The synergism of extraction is understood as a joint action of two extractants, which results in the distribution coefficients exceeding those for each extractant used separately. Systems involving crown ethers were developed and the synergetic effects in the extraction of ions of cobalt, 136 manganese, 137 ± 139 palladium, 140 uranium(VI), 141 lanthanides and actinides, 142 ± 149 strontium and barium, 150 ± 153 cesium 25 and radium 154,155 were studied. Unfortunately, in the studies of synergism the major attention has been paid to quantitative parameters of the extraction process (calculation of extraction constants and distribution coefficients), while the reasons for this effect and its mechanism have rarely been discussed.…”
Section: B Methods For Increasing Extraction Efficiency and Nonconven...mentioning
confidence: 99%